2012
DOI: 10.1164/rccm.201109-1614oc
|View full text |Cite
|
Sign up to set email alerts
|

Acute Upper Airway Responses to Hypoglossal Nerve Stimulation during Sleep in Obstructive Sleep Apnea

Abstract: Rationale: Hypoglossal nerve stimulation (HGNS) recruits lingual muscles, reduces pharyngeal collapsibility, and treats sleep apnea. Objectives: We hypothesized that graded increases in HGNS relieve pharyngeal obstruction progressively during sleep. Methods: Responses were examined in 30 patients with sleep apnea who were implanted with an HGNS system. Current (milliampere) was increased stepwise during non-REM sleep. Frequency and pulse width were fixed. At each current level, stimulation was applied on alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 36 publications
5
50
1
2
Order By: Relevance
“…This study is consistent with previous work that increasing stimulation amplitudes increases airflow, until reaching a plateau at higher amplitudes [13]. The previously reported plateau effect in flow is probably explained by the plateau of airway size at the retrolingual area, as seen in this study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study is consistent with previous work that increasing stimulation amplitudes increases airflow, until reaching a plateau at higher amplitudes [13]. The previously reported plateau effect in flow is probably explained by the plateau of airway size at the retrolingual area, as seen in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Therapeutic applications using neuromuscular electrical stimulation of the hypoglossal nerve and genioglossus muscle have been designed and evaluated as a potential alternative to positive airway pressure therapy and upper-airway surgical procedures [6][7][8][9][10][11][12][13]. The therapy consists of an implanted, programmable neurostimulation system, with a stimulation electrode around the protrusor branches of the right hypoglossal nerve and a respiration sensor placed in the right intercostal space to detect respiration [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Key pathophysiologic causes likely include (1) an anatomically compromised or collapsible upper airway (high passive critical closing pressure of the upper airway [Pcrit]) (6); (2) inadequate responsiveness of the upperairway dilator muscles during sleep (minimal increase in EMG activity to negative pharyngeal pressure) (7,8); (3) waking up prematurely to airway narrowing (a low respiratory arousal threshold) (9-13); and (4) having an oversensitive ventilatory control system (high loop gain) (13)(14)(15). Indeed, small physiologic studies have demonstrated interventions that lower Pcrit (16)(17)(18), increase the electrical activity to genioglossus (19,20), increase the arousal threshold (9), or lower loop gain (21,22) can reduce OSA severity. However, these important pathophysiologic traits have not been measured collectively in afflicted individuals.…”
mentioning
confidence: 99%
“…Such an intervention may, therefore, improve the effectiveness of, and adherence to, other treatment mainstays, e.g., by reducing the absolute pressure required for effective nCPAP therapy, or the amount of jaw repositioning for effective oral appliance therapy. We also recognize that other strategies to increase tongue muscle tone via non-pharmacological means, e.g., surgically implanted upper airway stimulation devices 6–8 , may also prove effective for the treatment of OSA.…”
Section: Introductionmentioning
confidence: 99%